Reduction of hexavalent chromium (Cr6+) in welding fumes during stellite hard facing with GTAW process. (2020) - Raajesh Kannan, R.K.; Sivapirakasam, S.P.; Vishnu, B.R.; Rahul, M.; Mohan, Sreejith
Abstract: A novel technique to reduce emission during stellite hardfacing was developed with a single compound activating flux. The strategy of coating the precursor of nano alumina to the base material brought a noticeable reduction in Cr 6+ concentration. The optimum combination of process parameters which favoured the maximum reduction Cr 6+ concentration in the welding fumes at the source was arrived using Taguchi methodology of experimental design. The maximum reduction of Cr 6+ up to 34% was achieved from this novel technique.